Sistem Persamaan Linear dengan Metode Gauss Seidel - Bela Amelia (Jurnal Pustaka Cendekia Pendidikan, 2024)
A linear equation is an algebraic equation in which each term contains a constant or multiplication of a constant with a single variable. Systems of linear equations arise directly from real problems that require a solution process. Systems of linear equations can be solved by two methods. The first method is direct, which is usually called the exact method. These methods include inverse, elimination, substitution, LU decomposition, Cholesky decomposition, QR decomposition, Crout decomposition, and ST decomposition. The second method is usually known as the indirect method or iteration method, including the Jacobi iteration method, the Newton method, and the Gauss Seidel method. The Gauss-Seidel method is a method of solving simultaneous equations through an iteration process so that the actual value is obtained by using the initial value in the next process using a previously known value.